Reelin-Related Disturbances in Depression: Implications for Translational Studies - Caruncho, Hector J.; Brymer, Kyle; Romay-Tallón, Raquel; Mitchell, Milann A.; Rivera-Baltanás, Tania; Botterill, Justin; Olivares, Jose M.; Kalynchuk, Lisa E. (Frontiers in Cellular Neuroscience, 2016)
The finding that reelin expression is significantly decreased in mood and psychotic disorders, together with evidence that reelin can regulate key aspects of hippocampal plasticity in the adult brain, brought our research group and others to study the possible role of reelin in the pathogenesis of depression. This review describes recent progress on this topic using an animal model of depression that makes use of repeated corticosterone injections. This methodology produces depression-like symptoms in both rats and mice that are reversed by antidepressant treatment. We have reported that corticosterone causes a decrease in the number of reelin-immunopositive cells in the dentate gyrus subgranular zone, where adult hippocampal neurogenesis takes place; that down-regulation of the number of reelin-positive cells closely parallels the development of a depression-like phenotype during repeated corticosterone treatment; that reelin downregulation alters the co-expression of reelin with neuronal nitric oxide synthase; that deficits in reelin might also create imbalances in glutamatergic and GABAergic circuits within the hippocampus and other limbic structures; and that co-treatment with antidepressant drugs prevents both reelin deficits and the development of a depression-like phenotype. We also observed alterations in the pattern of membrane protein clustering in peripheral lymphocytes in animals with low levels of reelin. Importantly, we found parallel changes in membrane protein clustering in depression patients, which differentiated two subpopulations of naïve depression patients that showed a different therapeutic response to antidepressant treatment. Here we review these findings and develop the hypothesis that restoring reelin-related function could represent a novel approach for antidepressant therapies.